Polygonum hastatosagittatum Maniko (Polygonaceae): a new record for Nepal - Sharma, Indira (Journal of Plant Resources, 2008)
Polygonum hastatosagittatum Makino has been recorded as new addition to the flora of Nepal. The description and distribution of this newly recorded species are provided herewith. <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]-->Bulletin of the Department of Plant Resources Vol 30, 2008 pp 19